Rahmatullah Bukhari and the Contemporary Significance of His Ethical Views - Saodat Abdullaeva (Athena: Journal of Social, Culture and Society, 2026)
The article provides a philosophical analysis of the life, scholarly and literary activity, and ethical views of Rahmatullah Bukhari (Vazeh), a prominent representative of the scholarly and literary environment of nineteenth-century Bukhara. Although the thinker did not compose a separate ethical treatise, the ideas advanced in his tazkira "Tuhfat ul-ahbob fi tazkirat ul-as'hob" and other works reveal a coherent and consistent moral worldview. The study examines the criteria upon which Vazeh relied in evaluating literary figures, disclosing his system of virtues, including knowledge and enlightenment, scholarly honesty and objectivity, friendship and loyalty, and human dignity. The author's distinctive approach, which harmonizes Sufi ethics with a practical philosophy of life, is also considered within the context of the Eastern philosophical tradition. The article substantiates the practical relevance of Vazeh's legacy for contemporary spiritual and educational processes, particularly for cultivating the unity of knowledge and moral maturity in young people, promoting academic integrity, and fostering national identity.